Etnografi Khalayak Pada Pengguna Sosial Media Tiktok (Studi Generasi Z Kota Serang) - Zulfikar, Meiby; Briandana, Rizky; Fitrianti, Rizqi; Suryasuciramdhan, Arfian; Kamilah, Fitrotul (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2024)
The reaction to the development of information and communication technology gave birth to new media that succeeded in becoming an interesting object as a means of communication and entertainment that became an addiction for its users, social media such as having an attachment to the social aspect of humans, Tiktok became one of the most attractive social media for its users, the emergence of Tiktok encouraged acceleration globalization era. Generation Z is the generation born in 1995-2010. The popularity of tiktok, which can be found on other social media such as Facebook, Instagram and others, is a part that contributes to user interest. Addiction to tiktok content is not immediately seen as an experience for users to receive justifiable information. The attachment to social media tiktok seems to have become a new medium in the life of generation Z. Users see the reality of the world based on what information is on tiktok social media, this is a development as a new form that has existed before in print media, columns, billboards, billboards, traditional media and so on. The purpose of this research is to see the experience of tiktok users in generation Z as a form of self-concept for its users. The research was conducted qualitatively with an audience ethnography method using a constructivist paradigm with an interpretative type. The interpretative paradigm is used to see the point of view of facts as something different that has context and meaning, looking at the experience of tiktok social media users on the user's self-concept.